Pengaruh Solvabilitas, Likuiditas dan Profitabilitas dengan Moderasi Good Corporate Governance terhadap Manajemen Laba pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Najib, Muhammad Ali; Hizazi, Achmad; Olimsar, Fredy (Universitas Batanghari Jambi, 2025)
This research aims to evaluate the relationship between variables, the analysis was carried out using the Moderated Regression Analysis (MRA) approach using quantitative methods and purposive sampling techniques. The research results show that only liquidity has a significant effect on earnings management, and there is no significant correlation between solvency and profitability. In addition, Good Corporate Governance (GCG) has been proven to be able to strengthen the relationship between liquidity and earnings management, but does not act as a moderator in the relationship between solvency and profitability and earnings management.